PLEURAL ENDOMETRIOSIS: BLOODY PLEURAL EFFUSION IN A 28-YEAR-OLD FEMALE WITH PRIMARY INFERTILITY (CASE REPORT) - Saheer, S.; Paul, A.; James, P.; Palak, R. (International Journal of Medicine and Medical Research, 2021)
Background. Endometriosis is defined as presence of endometrial glands outside the uterine cavity and it most commonly involves the structures within the pelvic cavity. Thoracic endometriosis syndrome usually presents as pneumothorax, hemoptysis, hemothorax or pulmonary nodules. Endometriosis presenting as hemorrhagic pleural effusion is rarely reported. Objectives. The aim of the study was to describe pleural endometriosis presenting as hemorrhagic pleural effusion and to insist on the role of medical thoracoscopy in making the diagnosis with the help of a case report. Methods. A case report of pleural endometriosis as a non-resolving hemorrhagic pleural effusion is presented. Results. A 28-years old female on treatment for her primary infertility presented with non-resolving bloody pleural effusion and she was on empirical anti-tubercular drugs for the last four months. Medical thoracoscopy revealed flat brownish grey plaques over the diaphragmatic pleura and the histology of pleural tissue revealed pleural endometriosis. She was initiated on gonadotropin releasing hormone-leuprolide and there was some clinico-radiological improvement. Conclusions. Thoracic endometriosis should be considered as one of the differentials for pleural effusion in female patient especially on treatment for infertility. Medical thoracoscopy should be the investigation of choice for evaluating pleural effusions before initiating empirical treatments.